Cathepsin A upregulation in glioma: a potential therapeutic target associated with immune infiltration: CTSA in glioma - Zhang, Ming; Huang, Jun; Wang, Yunfei; Nie, Qingbin; Zhang, Xinye; Yang, Yufeng; Mao, Gengsheng (Journal of Medical Biochemistry, 2022)
Backgrounds: Glioma is the result of malignant transformation of glial cells in the white matter of the brain or spinal cord and accounts for approximately 80% of all intracranial malignancies. Cathepsin A (CTSA) is highly expressed in a variety of tumor tissues, but its role in glioma is poorly studied. This study analyses the relationship between CTSA, and glioma based on TCGA Methods: Data for glioma patients were collected from TCGA and the expression level of CTSA was compared between paired glioma tissues and normal tissues with Wilcoxon rank-sum test. In addition, the Wilcoxon rank-sum test was also applied to analyze the relationship between clinicopathologic features and CTSA expression. Kaplan-Meier Plotter was applied to analyze OS, DSS and PFI. Immuno-infiltration analysis of BLCA was performed by single sample gene set enrichment analysis (ssGSEA) in the "GSVA" R package. Results: The CTSA was overexpressed in glioma tissues compared to normal tissues (P<0.001). The high expression of CTSA was significantly related to 1p/19q codeletion, IDH, WHO grade and histological type. Kaplan-Meier survival analysis showed that patients with glioma characterized with high expressed CTSA had a poorer OS (HR=2.16 P<0.001), DSS (HR=2.17 P<0.001) and PFI (HR=1.48 P<0.001) than patients with low CTSA expression. Moreover, High expressed CTSA was associated with immune cell infiltration Conclusion: CTSA may serve as a candidate prognostic biomarker for determining prognosis associated with immune infiltration in glioma cancer.